PENGARUH KEPEMILIKAN ASING, DEBT DEFAULT DAN AUDIT LAG TERHADAP OPINI AUDIT GOING CONCERN DENGAN SPESIALISASI AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Jasa Yang Terdaftar Di BEI Periode 2016-2018) - Aslam Imam Zacky; Rasuli M; Natariasari Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze foreign ownership, debt default and audit lag on going concern audit opinion with auditor specialization as moderated variable. The objects of this research are the service company at listed on BEI period 2016-2018. The data were analyzed by linear regression method and SPSS program version versi 17. The variable under study is going concern audit opinion as dependent variables, foreign ownership, debt default and audit lag as independent variables and auditor specialization as moderated variables. The results of the study show that foreign ownership has an influence affect on going concern audit opinion with a significance value of 0,014, debt default has an influence affect on going concern audit opinion with significance value of 0,002, audit lag has an influence affect on going concern audit opinion with significance value of 0.000, and audit lag after moderated specialitazion auditor has an influence affect on going concern audit opinion with significance value of 0.047, but specialization auditor has not succesfull as moderated variables for relationship between going concern opinion with foreign ownership and debt default. The results of this study also show that the coefficient of R square is 76,3%. Each independent variable, giving a strong influence on the dependent variable, meaning that the independent variable can explain dependent variable well. While the rest is influenced by other variables not included in the regression model is not included in this study.Keywords : Going Concern Audit Opinion, Foreign Ownership, Debt Default, Audit Lag, AuditorSpecialization